A Guidebook to Hunting Charged Higgs Bosons at the LHC - Arhrib, Abdesslam; Benbrik, Rachid; Harouiz, Hicham; Moretti, Stefano; Rouchad, Abdessamad (Frontiers in Physics, 2020)
We perform a comprehensive global analysis in the Minimal Supersymmetric Standard Model (MSSM) as well as in the 2-Higgs Doublet Model (2HDM) of the production and decay mechanisms of charged Higgs bosons (H^±) at the Large Hadron Collider (LHC). Starting from the most recent experimental results (SM-like Higgs boson signal strengths and search limits for new Higgs boson states obtained at Run-1 and -2 of the LHC and previous colliders), from (both direct and indirect) searches for Supersymmetric particles as well as from flavor observables (from both e^+e^- factories and hadron colliders) and upon enforcing theoretical constraints (vacuum stability, perturbativity, unitarity), we present precise predictions for H^± cross sections and decay rates in different reference scenarios of the two aforementioned models in terms of the parameter space currently available, specifically mapped over the customary (m_A,H^±, β) planes, including singling out specific Benchmark Points (BPs) amenable to phenomenological investigation. These include the m_h^mod+ and hMSSM configurations of the MSSM and the 2HDM Type-I, -II, -X and -Y. Such BPs are always close to (or coinciding with) the best fits of the theoretical scenarios to experimental data. We also briefly discuss the ensuing phenomenology for the purpose of aiding future searches for such charged Higgs boson states.